Pengaruh Pencucian Benih dengan Penambahan Fungisida terhadap Tingkat Serangan Penyakit Bulai, Pertumbuhan, dan Hasil Jagung Hibrida Varietas P27 - Fai Rachman; Ellen Rosyelina Sasmita; Suyadi Wongsowijoyo (Universitas Sebelas Maret, 2019)
Corn is an important food crop in the world. Downy mildew as a corn main disease causes a decrease of crop yields. Downy mildew can be prevented by seed treatment. The study aims to determine the effect of washing and adding fungicides on seeds to downy mildew attack, growth, and hybrid corn yields. The research conducted in Wedomartani Experimental Field, Ngemplak, Sleman with experiment in June – October 2018. Field experiment with Randomized Complete Block Design (RCBD) was set up, using single factor, which is seeds of P27 variety washed and added fungicides. There are 10 treatments: control, washed seeds, washed seeds + fungicide metalaxyl 3g/kg + dimetomorph 2g/kg, washed seeds + fungicide metalaxyl 3g/kg + dimetomorph 3g/kg, washed seeds + fungicide metalaxyl 3g/kg + dimetomorph 4g/kg, washed seeds + fungicide metalaxyl 3g/kg + dimetomorph 5g/kg, washed seeds + fungicide metalaxyl 5g/kg + dimetomorph 2g/kg, washed seeds + fungicide metalaxyl 5g/kg + dimetomorph 3g/kg, washed seeds + fungicide metalaxyl 5g/kg + dimetomorph 4g/kg, washed seeds + fungicide metalaxyl 5g/kg + dimetomorph 5g/kg. The results showed that control effective to prevent downy mildew attack, increasing growth and hybrid corn yields. Washed seeds cause high level of downy mildew attack, slow growth, and low crop yields. Seed treatments with fungicides is not effective, because give same affect with control.